UJI VALIDITAS DAN REABILITAS THE NEUROLOGICAL DEPRESSION DISORDERS INVENTORY FOR EPILEPSY NDDIE VERSI INDONESIA - Izati Rahmi, Astri Budikayanti, Diatri Nari Lastri,Herqutanto (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION DEPRESSION IS A COMMON PSYCHIATRIC DISORDER IN EPILEPSY IT IS A COMORBID CONDITION THAT ADVERSELY DECREASE PATIENTS HEALTHRELATED QUALITY OF LIFE AND ALSO POTENTIALLY LEAD TO THE EMERGENCE OF SUICIDAL HABITS IN PEOPLE WITH EPILEPSY SO IT REQUIRED AN INSTRUMENT THAT IS BRIEF AND ACCURATE IN INDONESIAN VERSION FOR DETECTION OF DEPRESSION IN PEOPLE WITH EPILEPSY